EMG and joint angular displacement during running at different terrain and ground surface conditions - Nilsson, J.; Gjerset, A.; Johansen, E.; Lund, M. (LASE Journal of Sport Science, 2013)
The purpose was to study joint angular displacement and myoelectric activity (EMG) of the hip, knee and ankle extensor muscles during running in different terrain-surface-gradient (TSG) settings at competition speed. In total six male regional to national level elite orienteers participated in the study. Mean (range), height and weight were 25 (19-32) years, 180 (1.74- 1.88) m and 71 (67-75)kg. Joint angular displacement was determined by electrogoniometers taped over the hip, knee and ankle joints of the right leg. Surface electrodes were used to record the EMG activity in m. gluteus maximus, m. vastus lateralis and m. soleus. The data was recorded by means of a data logger at 1000Hz and stored for later computer analysis. The participating orienteers performed runs in six different TSG settings: forest, forest uphill, forest downhill, timber felling, wet moss and gravel road. The time in each TSG setting was recorded by means of an ultra-sound based timing unit and the mean speed was calculated. The results showed a mean perceived competition speed in all test conditions of approximately 5 m•s-1 with the exception of wet moss and forest uphill which showed a competition speed of about 3 m•s-1. Despite of this the cycle duration in the different TSG settings was not significantly different. The basic angular displacement pattern was consistent in most TSG settings with exception of forest uphill and wet moss. The mean EMG activation level differed between the TSG settings. It can be concluded from the results in this study that different TSG settings put specific demands on joint angle amplitude and muscle action as well as activation, which has to be taken under consideration in the training design.